INCREASE OF AUTHENTICITY OF PROCEEDING IN INFORMATIVE STREAMS - Юдін, О. К.; Луцький, М. Г.; Чунарьова, А. В. (Science-based technologies, 2009)
The article shows the increasing confidence of correct identification code word based on the minimally sufficientinformation, based on models developed statistical procedures for critical decision-making rules. Assessment ofthe effectiveness of the newly introduced method, based on the calculation of analytical dependence of theprobability of correct identification and the probability of errors.